UTILIZATION OF CETHO TEMPLE FOR RELIGIOUS ACTIVITIES - Budiana Setiawan (Perkumpulan Organisasi Profesi DPP Dosen Hindu Indonesia (DHI) Bekerja sama dengan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar dan Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
According to the Law of the Republic of Indonesia Number 5 of 1992 concerning Cultural Heritage Objects, Cetho Temple was considered a dead monument, so it cannot be used for religious activities by Hindus. The discourse had changed since the issuance of the Law of the Republic of Indonesia Number 11 of 2010 concerning Cultural Heritage. Nevertheless, in its implementation, regulations have been needed for the interest of regulating the utilization of Cetho Temple as a national level of cultural heritage. In this regard, the problems in this study are: (1) How are the licensing arrangements of utilization of Cetho Temple for religious activities, both by the government of Republic of Indonesia and the government of Karanganyar Regency? (2) What are the benefits of licensing the utilization of Cetho Temple for Hindus and the community around the location of Cetho Temple? This study uses a qualitative method with a case study approach. Research data collection is done through literature review, in-depth interviews, and observation. The results showed that the Government of Karanganyar Regency since 2005 has given permission to Hindus to use the temple as a place of religious ceremony. The ceremonies that are held include: Galungan, Kuningan, Tawur Agung Kesanga, and Mondosiyo. As a consequence of the implementation of the local regulations, at Cetho Temple there is a division of management authority between the Agency of Tourism Youth and Sports of Karanganyar Regency and the Office of Cultural Heritage Conservation of Central Java. The Agency of Tourism Youth and Sports of Karanganyar Regency manages tourists who come to Cetho Temple, especially for ticket sales arrangements. The Office of Cultural Heritage Conservation of Central Java manages the conservation activity at the temple, which is financed using the state budget. The utilization of Cetho Temple as a place of religious ceremony for Hindus will actually enliven tourism activities.